Fracture resistance of simulated immature teeth after different intra-radicular treatments - Sivieri-araujo, Gustavo; Tanomaru-filho, Mario; Guerreiro-tanomaru, Juliane Maria; Bortoluzzi, Eduardo Antunes; Jorge, Érica Gouveia; Reis, José Maurício Dos Santos Nunes (Fundação Odontológica de Ribeirão Preto, 2015)
The aim of this study was to evaluate the fracture resistance of simulated immature teeth after different intra-radicular treatments. Crowns and roots of bovine incisors were cut transversally and removed to simulate immature teeth. Root canal preparation and flaring were performed using a bur in crown-apex and apex-crown direction. The samples were distributed into 5 groups (n=10): Positive control (PoC) - no root canal flaring or filling; Negative control (NeC) - teeth were sectioned and their root canals were flared; Direct anatomical glass fiber post (RaP) - #2 Reforpost main glass fiber post relined with composite resin; Double tapered conical glass fiber posts (ExP) - #3 Exacto glass fiber post; and #2 Reforpost main glass fiber + Reforpin accessory glass fiber posts (RrP). In RaP, ExP and RrP, 4.0-mm apical plugs were done with MTA Angelus. The specimens were embedded in polystyrene resin inside cylinders and the periodontal ligament was simulated with a polyether-based impression material. The specimens were submitted to compressive fracture strength test (0.5 mm/min at 135° relative to the long axis of the tooth) in a servo-hydraulic mechanical testing machine MTS 810. Data were subjected to one-way ANOVA and Dunnett's C or Tukey's tests (α=0.05). The control groups (PoC and NeC) showed lower fracture strength than the experimental groups. NeC presented the lowest resistance and ExP presented the highest resistance among the experimental groups. The flaring procedures produced a detrimental effect on the fracture resistance of the bovine teeth. Glass fiber intra-radicular posts increased significantly the fracture resistance of simulated immature teeth.

O objetivo deste estudo foi avaliar a resistência à fratura de dentes com rizogênese incompleta simulada após diferentes tratamentos intra-radiculares. A rizogênese incompleta foi simulada pelo seccionamento das coroas e raízes de incisivos bovinos. O preparo e alargamento do canal radicular foram realizados utilizando uma broca no sentido coroa-ápice e ápice-coroa. As amostras foram distribuídas (n=10) em cinco grupos: controle positivo (PoC) - sem preparo do canal radicular e sem obturação; controle negativo (NeC) - os dentes foram seccionados e os canais radiculares foram preparados; pino anatômico direto Reforpost #2 (RaP) - pino de fibra de vidro principal + resina composta; pino de fibra de vidro com dupla conicidade (ExP) - pino de fibra de vidro Exacto #3; e pino de fibra de vidro Reforpost #2 + pinos de fibra de vidro acessórios Reforpin (RrP). Nos grupos RaP, ExP e RrP foram realizados plugs apicais de MTA Angelus com 4,0 mm. As amostras foram incluídas em cilindros com resina de poliestireno e o ligamento periodontal foi simulado com material de moldagem à base de poliéter. As amostras foram submetidas ao teste de resistência à fratura, por meio de força compressiva (0,5 mm/min a 135º em relação ao longo eixo do dente) em uma máquina de ensaios mecânicos MTS 810. Os dados foram submetidos à ANOVA a um critério e aos testes para comparações múltiplas Dunnett C ou Tukey HSD (α=0,05). Os grupos controle (PoC e NeC) apresentaram resistência à fratura inferior aos grupos experimentais, sendo o menor valor médio produzido por NeC. ExP produziu os maiores valores de resistência à fratura entre os grupos experimentais. Os procedimentos de preparo e alargamento produziram efeitos prejudiciais na resistência à fratura de dentes bovinos. A utilização de pinos de fibra de vidro intra-radiculares aumentou significativamente a resistência à fratura de dentes com rizogênese incompleta simulada.
Keywords: Endodontically treated teeth; Immature teeth; Glass fiber post; Racture resistance